ROLE OF PUBLIC DISTRIBUTION SYSTEM IN TO PURGE POVERTY IN PALAKKAD DISTRICT: ISSUES AND CHALLENGES - R SHAJI and SHERLY THOMAS
India is home to 22 per cent of the world’s poor. Such a high incidence of poverty is a matter of concern in view of the fact that poverty eradication has been one of the major objectives of the development planning process. Indeed, poverty is a global issue. Reduction of poverty in India is, therefore, vital for the attainment of international goals. Poverty alleviation has been one of the guiding principles of the planning process in India. PDS is primarily a social welfare and antipoverty programme of the Government of India. Essential commodities like rice, wheat, sugar, kerosene and the like are supplied to the people under the PDS at subsidized prices. The PDS in India was criticized on a wide front its failure to serve the Below Poverty Line (BPL) population, for its perceived urban bias, negligible coverage in States with a high density of rural poor and finally, the lack of transparent and accountable arrangements for delivery. Thus from June 1997 PDS turned into the Targeted Public Distribution System (TPDS), with the aim of targeting the poorest household by differentiating the access quantities and prices at which one is allowed to buy. In this paper, an attempt has been made to assess the role of public distribution system to eradicate poverty and the problems behind it. For this palakkad district in kerala is selected as study area.100 PDS beneficiaries are interviewed using questionnaire containing all relevant queries.